Pewarisan Seni Rapa’i dabo’ih sebagai Reproduksi Budaya di Perkampungan Bekas Evakuasi Pascatsunami Aceh - Fani Dila Sari; Beni Andika (LP2M ISBI Bandung, 2020)
ABSTRACTThe evacuation of victims of the Aceh tsunami in 2004 in the CARE refugee camps formed sociology as a new community despite having different ethnographic backgrounds from various parts of the Aceh coast. Interestingly, the cultural arts practices that exist in CARE village to date are the performing arts that developed in Pulo Aceh before the tsunami, namely Rapa’iDabo’ih. Seeing the symptoms of cultural reproduction is interesting to study because the refugees came from various regions in Aceh. The purpose of this study was to determine the factors of cultural reproduction and how to implement them in the art work of Rapa’i dabo’ih by the Bungong Sitangkee group. The research is qualitative research. Cultural reproduction in traditional arts through the presentation of the Rapa’i Daboih performance of the Sitangkee Group is the focus of this research. The theoretical basis used is the thought of cultural reproduction put forward by Pierre Bourdieu. The cultural reproduction of Rapa’i dabo’ih by the Bungong Sitangkee group is a system of cultural inheritance, namely the maintenance of knowledge and experience from one generation to the next.Keywords: Cultural Reproduction, Post-Tsunami, Rapa’i dabo’ih, Bungong Sitangkee Group, and CARE Evacuation.ABSTRAKEvakuasi korban tsunami Aceh tahun 2004 di pengungsian CARE membentuk sosiologi sebagai komunitas masyarakat baru meski memiliki latar belakang etnografi yang berbeda dari berbagai penjuru pesisir Aceh. Menariknya, praktik-praktik seni budaya yang eksis di perkampungan CARE hingga saat ini adalah seni pertunjukan yang berkembang di Pulo Aceh sebelum masa tsunami, yakni Rapa’i dabo’ih. Melihat gejala reproduksi budaya tersebut menjadi menarik untuk diteliti sebab para pengungsi berasal dari berbagai daerah di Aceh. Tujuan penelitian ini adalah untuk mengetahui faktor terjadinya reproduksi budaya dan bagaimana implementasinya dalam garapan seni Rapa’i dabo’ih oleh grup Bungong Sitangkee. Penelitian adalah penelitian kualitatif. Reproduksi budaya dalam kesenian tradisional melalui penyajian pertunjukan Rapa’i daboih Grup Sitangkee adalah fokus dalam penelitian ini. Landasan teoritis yang digunakan adalah pemikiran reproduksi budaya yang dikemukakan oleh Pierre Bourdieu. Reproduksi budaya Rapa’i dabo’ih oleh grup Bungong Sitangkee adalah sistem pewarisan budaya yaitu sebagai pemeliharaan pengetahuan dan pengalaman dari satu generasi ke generasi berikutnya.Kata kunci: Reproduksi budaya, Pascatsunami, Rapa’i dabo’ih, Grup Bungong Sitangkee, dan Pengungsian CARE.